Evaluating the safety profile of defibrotide in sickle cell disease: an in vitro study - Laura Bencheikh; Meghan Perkins; Kim Anh Nguyen; Clara Noizat; Anoosha Habibi; Marie Cambot; Pablo Bartolucci (Haematologica)
Not available.